BIOCOM, design of an ecofriendly and intelligent solution for the management of organic waste at home - Estrada-Ortiz, Elia (2019)
BIOCOM is a project that consists in the creation of a system of eco-friendly products, assisted by technology that accompanies users in the realization of composting and micro plantation activities inside their homes. For both intelligent systems a prototype was built, each one assembled with technological components such as temperature and humidity sensors, alerts, photoperiod guided lighting and automated mechanisms for composting. BIOCOM uses the Takakura composting method, based on the breakdown of organic waste through microorganisms that can be used for agriculture in order to enrich the soil. The prototypes sought to provide a practical solution to the existing problematic of post-use of organic waste that affect negatively the environment